(untitled) (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 68-78 to 71-81. BRRI prilled urea applicator was designed and developed to facilitate deep placement of regular urea. Experiments were conducted to evaluate the performance of BRRI prilled urea applicator in the farmers fields at Gosaidanga in Shailkupaupazila under Jhenaidah district and at Rashidpur in Mithapukurupazila under Rangpur district during Boro 2015 season. Three treatments: hand broadcasting of urea (recommended dose) (HB), BRRI prilled urea applicator (70% of the recommended dose) (PUA) and BRRI USG applicator (70% of the recommended dose) (USGA) were compared in the experiments. The experiment was laid out in randomized complete block design (RCBD) and replicated in four farmers plots in each location using BRRI dhan28 as test crop both the locations. Prior to field experiment, prilled urea applicator was calibrated and urea dispensed was set to 14 gm in one revolution of drive wheel for Boro season. The field capacity of the PUA and USGA was almost similar (0.09-0.10 ha hr-1) in both the locations. Field efficiency of PUA and USGA had 64-65 and 68-69 percent, respectively. PUA and USGA saved 29-32 percent urea fertilizer compared to HB whereas labour requirement of HB (3.74-4.04 man-hr ha-1) in three splits showed similar to single application of urea by PUA (3.68-4.00 man-hr ha-1) and USGA (3.78-3.97 man-hr ha-1). Urea application cost in HB, PUA and USGA was Tk 4,624, 3,216-3,424 and 3,305-3,483 per hectare in both the locations. Prilled urea application method reduced the production cost. Urea application methods showed insignificant effect on grain yield. BRRI prilled urea safely dispensed urea fertilizer in subsurface, increased the efficacy of urea fertilizer and saved urea fertilizer without sacrificing grain yield. BRRI prilled urea applicator could be a viable technology in rice cultivation. Extensive dissemination works should be undertaken in different agro-ecological zones for wide spread adoption of the applicator. Bangladesh Rice j. 2015, 19(2): 71-81